2020
DOI: 10.2174/2452271603666191016143811
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide Produced from Rhizobium spp. - An Interesting Product for Industry and Environment

Abstract: : Most legume species, such as soybeans, beans, and clover, have the ability to establish a symbiotic relationship with nitrogen-fixing bacteria in the soil, which promotes plant growth and productivity. Exopolysaccharide macromolecules are particularly necessary for binding the bacteria to root hairs and initiating the deformation of root hairs, thus trapping the bacteria to initiate root invasion through a tube-like infection thread. Very few studies have focused on the isolation and characterization of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2031
2031

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Researchers revealed that exopolysaccharide (EPS) are key components for the establishment of an effective symbiosis between leguminous plants and rhizobia [5]. Recently, non-toxic rhizobial EPS have been found to have properties suitable for application in various fields, including medicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers revealed that exopolysaccharide (EPS) are key components for the establishment of an effective symbiosis between leguminous plants and rhizobia [5]. Recently, non-toxic rhizobial EPS have been found to have properties suitable for application in various fields, including medicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…They are distributed on the chromosome or in symbiotic plasmids (Ivashina and Ksenzenko, 2012;Ormeño-Orrillo et al, 2012). EPS contain mostly D-glucose and D-galactose (Castellane et al, 2014(Castellane et al, , 2017(Castellane et al, , 2018(Castellane et al, , 2019, uronic acids and non-sugar substitutions can also be very important (López-Baena et al, 2016). Enzymes such as glycosyltransferase (PssA) and galactosyltransferase (PssJ) are responsible for assembling EPS sub-units in R. leguminosarum (Marczak et al, 2020).…”
Section: Importance Of Exopolysaccharides Production In Symbiosismentioning
confidence: 99%
“…Rhizobium produce different types of polysaccharides, these polysaccharides found on surface of rhizobial cell that important in establish specific symbiotic relationship between Rhizobium and leguminous plants (Janczarek et al, 2015;Ghosh and Maiti, 2016;de Oliveira et al, 2018;Castellane, et al, 2019 andCastellani et al, 2021). Also bacterial exopolysaccharides play an importance role in plant abiotic stress (Bhagat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%